Genetic and environmental contribution to phenotypic resemblance between Iranian couples: Tehran Cardiometabolic and Genetic Study (TCGS) - Parisa Riahi; Amir Hossein Saeidian; Albert Tenesa; Carolyn T. Hogan; Michael March; Kamran Guity; Mahmoud Amiri Roudbar; Asieh Zahedi; Maryam Zarkesh; Farideh Neshati; Mehdi Hedayati; Fereidoun Azizi; et al. (Heliyon)
Objective: To provide an applied framework for assessing the genetic contribution to assortative mating (AM) using height as a model trait and disclose the trace of certain pieces of evidence of AM in the form of the shared environmental effects from long-term cohabitation on spouses’ anthropometric traits and lipid serum levels. Methods: 2315 genotyped couples were extracted from the Tehran Cardiometabolic Genetic Study (TCGS). Pearson correlation analysis was used to assess the relationship between spouses' height. The GCTA-GREML was used to assess the SNP-based heritability of individual and spousal heights with AM adjustments. We used a recent GWAS meta-analysis of ∼5.4M individuals of height to calculate polygenic risk scores (PRS) for spouses’ height. A subset of 1038 spouses out of 2315 couples were subsequently selected to enter the longitudinal resemblance, to be assessed in terms of their anthropometric traits and lipid serum levels in a 15-year follow-up. We conducted a Bayesian hierarchical meta-analysis for each time point to assess the validity of the increasing trend of the longitudinal association. Results: The correlation coefficient of height between spouses was estimated as r = 0.248. We found that a person's genotype determines 6.15 % of the variation in the spouse's height. Furthermore, correlation between PRS of individuals showed a statistical association between an individual’s genotype and their spouse’s genotype (R2 = 4 %) across 1,982 couples with only one genotyped spouse, achieving approximately half of the theoretical maximum accuracy. Long-term spousal resemblance revealed an increasing trend for correlation between husbands and wives in terms of their lipid serum level and obesity-related traits. Conclusion: Our findings support the AM hypothesis for height with a significant spousal correlation and show that selecting the spouse's height is genetically determined. Besides, we provide data showing that AM is predicted to result in a10 % increase in the heritability of height, which is related to the assortative nature of alleles in the population and not to the segregation of genetic variations. Finally, as one of the evolutionary consequences of AM, long-term spousal resemblance provided an increasing trend for correlation between spouses in terms of their lipid serum level and obesity-related traits.